Xử lý băng địa chấn bị nhiễu bằng phương pháp thống kê - Vinh, Nguyễn Đức; Thăng, Nguyễn Công (Journal of Computer Science and Cybernetics, 2016)
It is generally recognized that geophysical data, especially with seismic data always mixed by noisy signal. Therefore, filtering is one of the most important work in the interpretation of seismic data. This paper presents some  filtering  technique for  interpreting seismic data based on statistical methods.